Laser Biostimulation Effect on Human Sperm Motility - mohammed, sama emad; H. Al-ameri, Layla M. (Iraqi Journal of Laser, 2021)
Background: Sperm motility disorder is an important cause of infertility in male, and one of the causes of reduced motility of the sperm is the disorders of the mitochondria because it provides the required energy for sperm motility, Laser biostimulation or low-level laser therapy has a positive effect on the mitochondria and led to increasing the synthesis of ATP. Method: Twenty fresh human semen samples were used in this research study, each sample was separated into two portions, one was used as control which is not exposed to the laser beam and the other was irradiated with the wavelength of 410 nm diode laser with an output power of 100 mW and an exposure time of 60 seconds, then the measurement of the progressive motility, non-progressive motility, and the immotile sperm were assessed after 5,15,30 min of irradiation for every control and the irradiated samples. Results: the progressive and non-progressive motility of the sperm was significantly increased following irradiation compared to the control samples also the number of immotile sperm was significantly decreed after irradiation. Conclusion: We observed that a low-power laser of 410 nm wavelength could cause sperm motility to increase for a short time.